An IoT-enabled health monitoring system for hypertension and cardiovascular risk management - Azidin, Farid Arafat; Abdul Rahman, Ahmad Idil; Zainudin, Zulkarnain; Mohd Idris, Niza; Sabray @ Sabri, Nur Aisyah Sofia (Human Resource Management Academic Research Society, 2025)
This study presents the development of an IoT-enabled healthcare monitoring system designed to provide continuous measurement of heart rate and blood pressure for individuals at risk of hypertension and cardiovascular diseases. The system integrates the MAX30102 sensor with the ESP8266 microcontroller to capture real-time health parameters, which are displayed on an LCD panel and synchronized with a mobile application developed using MIT App Inventor. To enhance user safety, a buzzer and LED indicator are incorporated to issue alerts during abnormal readings, allowing timely response and intervention. Beyond its technical functions, the system contributes to healthcare management by promoting accessibility, comfort, and self-monitoring practices. By enabling patients to take greater responsibility for their own health, the solution strengthens preventive healthcare, supports early diagnosis, and encourages awareness of chronic disease risks. This research highlights the broader implications of IoT integration in healthcare, emphasizing its role in improving resource efficiency, empowering patients, and supporting sustainable health systems in the digital era.